A comparison of the views of modern scholars on the origin, date and importance for O.T. study of the Dead Sea Scrolls - Sheriffs, Robert J A (Rhodes University, Faculty of Divinity, Department of Divinity, 1954)
In the early part of 1948 an announcement was made concerning the discovery of some ancient manuscripts in Palestine; to this discovery sober and distinguished scholars applied adjectives like 'sensational' and 'phenomenal' - words that not commonly applied to the discovery of manuscripts in the world of scholarship.
Keywords: Dead Sea scrolls